Protocells: Milestones and Recent Advances. Issue 18 (23rd March 2022) - Gözen, Irep; Köksal, Elif Senem; Põldsalu, Inga; Xue, Lin; Spustova, Karolina; Pedrueza‐Villalmanzo, Esteban; Ryskulov, Ruslan; Meng, Fanda; Jesorka, Aldo
Abstract: The origin of life is still one of humankind's great mysteries. At the transition between nonliving and living matter, protocells, initially featureless aggregates of abiotic matter, gain the structure and functions necessary to fulfill the criteria of life. Research addressing protocells as a central element in this transition is diverse and increasingly interdisciplinary. The authors review current protocell concepts and research directions, address milestones, challenges and existing hypotheses in the context of conditions on the early Earth, and provide a concise overview of current protocell research methods. Abstract : A review of the state of the art in protocell research is presented, following a concise overview of early Earth conditions relevant to protocell development. Compartment concepts, progress in experimental and theoretical research on protocell models, as well as fabrication technologies are summarized. The TOC image was inspired by a painting by W. Kandinsky.